Integrated gradient polyurethane foam material and preparation method thereof
Through one-step chemical foaming by pressure-assisted foaming technology, the problem of high dependence and high energy consumption in the existing technology of gradient polyurethane foam equipment is solved, and the continuous transition between density and cell size is achieved, and the compressive strength of the material is improved. and specific energy absorption performance reduces cost and energy consumption.
Patent Information
- Application Number
- CN202411372947.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The prior art has problems such as high equipment dependence, high energy consumption, high cost and poor interfacial stress transmission when preparing gradient polyurethane foam materials, resulting in insufficient material performance.
One-step chemical foaming is used to mix the polyether polyol, foaming agent, chain extender, crosslinking agent, foaming agent and catalyst to apply constant or step-by-step loading to achieve integrated gradient foam The preparation of the product avoids interface problems and high energy consumption.
The continuous transition between density and cell size is achieved, the production cost and energy consumption of the material are reduced, the compressive strength and specific energy absorption performance of the material are improved, and the energy absorption efficiency reaches more than 97.77%.
Smart Images

Figure CN119241801A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an integrated gradient polyurethane foam material and a preparation method thereof, belonging to the technical field of foam materials. Background Art
[0002] Polyurethane foam (PUF) is a microporous foam material. Its uniform and fine pore structure gives it high strength, good toughness, and smooth stress transmission. Therefore, it is widely used in shoemaking, cushioning, and explosion-proof materials. PUF can dissipate energy through the recoverable deformation of the matrix and pore structure, especially in shock absorption. A large number of studies have shown that the mechanical properties of foam are closely related to its relative density and pore morphology. However, the overall characteristics of homogeneous foam are flattened, and improving energy absorption performance often means increasing foam density and material costs. Therefore, gradient foams with hierarchical pore structures have gradually become a research focus.
[0003] Gradient foam material is a new type of porous composite material with a continuous gradient change in composition and structure. The design requirements of its overall function and performance can be met by optimizing the structure. The existing preparation methods of polymer gradient foam materials are:
[0004] (1) The bonding method (CN110696440A, document “Preparation and Performance Study of Gradient Density Polyurethane Foam Plastics”) bonds single-layer materials of different properties together to construct a gradient foam. The above method is simple, but there are interface problems that cannot be ignored. It does not belong to integrated preparation. In addition, due to the existence of a bonding layer with a sudden change in density, it is difficult for stress to continue to be transmitted across the strong interface, resulting in stress first cohesion at the interface and generating lateral shear tearing at this location, leading to crush failure.
[0005] (2) The supercritical foaming method (CN110204778A, CN108795052A, CN108164831A, CN106336522A) requires the gas saturation adsorption of thermoplastic materials under high temperature and high pressure conditions, and then forms gradient bubbles through two-stage adsorption or two-stage pressure release processes. This method has high energy consumption and strict requirements on equipment.
[0006] (3) 3D printing method (CN109376497A, CN107200583A) prepares gradient foam by printing molten wire along a predetermined path. The path control of this method is relatively complex, the variability of the foam cells is not high, and the production capacity is not high due to the limitation of printing speed.
[0007] (4) Freezing method (CN109180992A) uses directional freezing method to prepare gradient aerogel material. This method requires cold and hot treatment, has high energy consumption and low production capacity.
[0008] (5) Melt co-extrusion method (CN108164814A) After the base material and the nucleating agent in different proportions are mixed and extruded into sheets, the sheets are melted and overlapped. Since the nucleating agent is conducive to the formation of bubbles, the pore distribution is positively correlated with the concentration of the nucleating agent. This characteristic is used to obtain a gradient porous material after foaming. This method is cumbersome and has high energy consumption.
[0009] (6) The microwave method (CN117820714A) is similar to melt coextrusion. It uses substrate sheets containing different concentrations of microwave absorbers to melt and overlap, and then obtains a gradient foam material after pre-foaming and microwave secondary foaming. Due to the difference in microwave absorber concentration, a gradient temperature field can be formed, which affects the foaming degree and forms a gradient foam. This method is more complicated, requires more stringent equipment conditions, and has high energy consumption.
[0010] Although the above methods can all construct gradient foam materials, they all have some limitations, resulting in insufficient development of gradient foam materials.
[0011] Therefore, developing an integrated method for preparing gradient polyurethane foam materials to reduce dependence on equipment and further reduce production costs has extremely high practical and economic value. Summary of the invention
[0012] To solve the above problems, the present invention uses pressure-assisted foaming technology to prepare integrated gradient foam by one-step chemical foaming. The technical method adopted by the present invention is simple and easy to reproduce, and can achieve the purposes of reducing energy consumption, reducing costs or improving efficiency. The gradient foam material prepared by the present invention achieves a continuous transition between density and pore size, avoiding internal damage caused by interface problems.
[0013] A first object of the present invention is to provide a method for preparing an integrated gradient polyurethane foam, the method comprising:
[0014] (1) mixing a polyether polyol, a blowing agent, a chain extender, a crosslinking agent, a foaming agent and a catalyst to obtain a prefabricated material; mixing the prefabricated material and an isocyanate to obtain a foamed material;
[0015] (2) pouring the foaming material into a mold, applying a load to the surface of the foaming material in the lifting direction as the action surface; after the load is applied, free foaming is performed; after the foaming is completed, taking out the foam sample, and ripening it to obtain an integrated gradient polyurethane foam;
[0016] Among them, the load intensity during the load action is 8 to 12 bar, the constant load is 2 to 10 seconds, and the free foaming is 0 to 8 seconds (constant load method);
[0017] or,
[0018] During the load action, the load intensity starts from 0 bar, and the load intensity changes at a rate of 0.8 to 4.0 bar / s, with a gradient load of 2 to 10 s and free foaming of 0 to 8 s (step load method).
[0019] In one embodiment, the blowing agent is water; preferably, the blowing agent is industrial grade deionized water.
[0020] In one embodiment, the chain extender is one or both of ethylene glycol and 1,4-butanediol.
[0021] In one embodiment, the cross-linking agent is diethanolamine.
[0022] In one embodiment, the foam leveling agent is silicone oil.
[0023] In one embodiment, the catalyst is one or more of triethylenediamine, Tegoamin DMEA, and A33.
[0024] In one embodiment, the period from when the foaming material is poured into the mold to when the foaming material gels is called the processing window period; the duration of the processing window period is closely related to the properties of the substrate (foaming material) and is affected by the feed ratio; in the present invention, the processing window period is the sum of the duration of the foaming material loading and the duration of free foaming, that is, the operation time, which is 5 to 20 seconds;
[0025] Preferably, the processing window is 10 s.
[0026] In one embodiment, in step (1), the mass ratio of polyether polyol, blowing agent, chain extender, crosslinking agent, foam leveling agent and catalyst is 90-110:0.65-0.85:4-6:2-4:0.3-0.7:1.5-2.
[0027] In one embodiment, it is characterized in that, in step (1), the mass fraction ratio of the prefabricated material to the isocyanate is 98.45-123.55:75:86.5.
[0028] In one embodiment, in step (2), the aging is performed by placing the foam sample at 40-70° C. for 48-72 hours.
[0029] The second object of the present invention is to provide an integrated gradient polyurethane foam prepared by any of the above methods.
[0030] The third object of the present invention is to provide application of any of the above methods or the above integrated gradient polyurethane foam in the field of materials.
[0031] In one embodiment, the application in the field of materials includes: preparing building materials, furniture, packaging materials, protective equipment, medical equipment, and sports equipment.
[0032] A fourth object of the present invention is to provide a pad for impact protection, the pad containing the above-mentioned integrated gradient polyurethane foam.
[0033] A fifth object of the present invention is to provide a building material, which contains the above-mentioned integrated gradient polyurethane foam.
[0034] A sixth object of the present invention is a method for improving the compressive strength, specific energy absorption performance and impact resistance of a polyurethane foam material, the method comprising:
[0035] (1) mixing a polyether polyol, a blowing agent, a chain extender, a crosslinking agent, a foaming agent and a catalyst to obtain a prefabricated material; mixing the prefabricated material and an isocyanate to obtain a foamed material;
[0036] (2) pouring the foaming material into a mold, applying a load to the surface of the foaming material in the lifting direction as the action surface; after the load is applied, free foaming is performed; after the foaming is completed, taking out the foam sample, and ripening it to obtain an integrated gradient polyurethane foam;
[0037] Among them, the load intensity during the load action is 8 to 12 bar, the constant load is 2 to 10 seconds, and the free foaming is 0 to 8 seconds;
[0038] or,
[0039] During the load action, the load intensity starts from 0 bar, and the load intensity changes at a rate of 0.8 to 4.0 bar / s. The gradient loading time is 2 to 10 s, and the free foaming time is 0 to 8 s.
[0040] In one embodiment, in step (1), the mass ratio of polyether polyol, blowing agent, chain extender, crosslinking agent, foam leveling agent and catalyst is 90-110:0.65-0.85:4-6:2-4:0.3-0.7:1.5-2.
[0041] In one embodiment, it is characterized in that, in step (1), the mass fraction ratio of the prefabricated material to the isocyanate is 98.45-123.55:75-86.5.
[0042] In one embodiment, in step (2), the aging is performed by placing the foam sample at 40-70° C. for 48-72 hours.
[0043] Beneficial effects of the present invention:
[0044] The present invention utilizes pressure-assisted foaming technology to prepare integrated gradient foam by one-step chemical foaming. The preparation method of the present invention is simple, environmentally friendly, low-cost and highly efficient. The prepared integrated gradient foam has good performance and high strength.
[0045] Specifically:
[0046] (1) The integrated gradient foam prepared by the present invention under constant load has a compressive strength of more than 524 kPa; the specific energy absorption reaches 25 kJ / m 3 ·g and above, up to 124KJ / m 3 g; Energy absorption efficiency reaches over 97.77%;
[0047] (2) The integrated gradient foam prepared by the present invention through gradient loading has a compressive strength of more than 227 kPa; the specific energy absorption reaches 12 kJ / m 3 g, up to 103KJ / m 3 ·g; the energy absorption efficiency reaches over 98.13%. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is the scanning electron microscope image result of sample JT-1 prepared in Example 1.
[0049] Figure 2 This is the scanning electron microscope image result of sample JT-2 prepared in Example 2.
[0050] Figure 3 This is the scanning electron microscope image result of sample JT-3 prepared in Example 3.
[0051] Figure 4 This is the scanning electron microscope image result of sample LX-1 prepared in Example 4.
[0052] Figure 5 This is the scanning electron microscope image result of sample LX-2 prepared in Example 5.
[0053] Figure 6 This is the scanning electron microscope image result of sample LX-3 prepared in Example 6.
[0054] Figure 7 This is the scanning electron microscope image result of the sample JZ-PUF prepared in comparative example 1. DETAILED DESCRIPTION
[0055] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0056] The invention adopts mechanical pressure-assisted foaming technology, and the gas generated by chemical reaction forms bubbles during the agglomeration process. The technical key of the invention is that the externally applied pressure has a certain restrictive effect on the expansion of the bubbles, thereby causing the bubble structure to change significantly.
[0057] During the critical processing window, the molecular network structure has not yet fully solidified. At this time, the increase in viscosity gives the cell wall a certain strength. Although this strength is still in a relatively fragile and easily deformed state, the external load applied to the matrix prompts the gas in the cell to resist the deformation and contraction caused by the external pressure from the inside to the outside until a dynamic equilibrium is reached. The result of this equilibrium state is that the cell bends and deforms, forming an oblate structure. In addition, due to the continuity of stress transmission, the degree of bending deformation of the cell gradually decreases from the outside to the inside, forming a natural gradient structure. With the enhancement of stress conduction, the thickness of the dense area will gradually accumulate and increase under the same pressure action time.
[0058] In this integrated gradient foam, a continuously increasing cell size distribution appears. In the dense zone, the cells are elliptical, small in size, and high in density; while in the conventional zone, the cells are nearly circular, large in size, and low in density. These two distinct morphological characteristics give the elastomer unique physical properties. In the dense zone, due to the thicker cell walls, energy is dissipated mainly through bending deformation during compression; while in the conventional zone, the cell walls are thinner and often accompanied by tearing to dissipate energy. This thicker dense zone design effectively reduces the risk of matrix tearing during impact. At the same time, the presence of the conventional zone significantly improves the overall specific energy absorption capacity of the material.
[0059] The present invention adopts two unique methods to efficiently manufacture integrated gradient foam. The first method is the constant load method, which stands out for its powerful load-assisted foaming effect, and can significantly increase the gradient difference of the foam, thereby creating a foam structure with significant gradient characteristics, improving the material's specific energy absorption performance while improving the material's impact and tear resistance; the second method is the step load method, which performs well in regulating the material's pore density, and it can effectively reduce the reverse propagation of stress waves, thereby significantly reducing the recoil effect during impact. These two methods have their own advantages and together provide strong technical support for the manufacture of high-performance gradient foams.
[0060] The integrated gradient foam described in the present invention has the characteristics of light weight, high strength, compression resistance, energy absorption and shock absorption. The preparation method is greatly simplified and does not require high temperature and high pressure to reduce energy consumption.
[0061] Test method:
[0062] 1. Microscopic morphology characterization
[0063] The cross-sectional cell structure was characterized using a scanning electron microscope (SEM) as follows:
[0064] (1) Cell size statistics: The cell size was counted using Image J software and the average value was recorded. The cell size of the gradient foam was the weighted average value of different regions in μm.
[0065] (2) Cell density statistics: The number of cells was counted using Image J software, and the average value was recorded. Cell density (N) is defined as the total number of cells per cubic centimeter of foam sample. The cell density of gradient foam is the weighted average of different regions, with a unit of 10 5 × cells / cm 3 .
[0066] (3) Open and closed porosity test: The gas replacement method is used to analyze the cell type using a fully automatic open and closed porosity analyzer to test the actual volume of the sample and then give the open and closed porosity of the sample in %.
[0067] 2. Compression and impact protection performance
[0068] (1) Compression resistance test:
[0069] According to GBT 6669-2008 "Determination of compression permanent deformation of soft foam polymer materials", the compression performance of the foam was tested using a microcomputer-controlled universal testing machine. Two test speeds were used for single-cycle quasi-static compression tests, with loading and unloading rates of 1mm / min and 10mm / min respectively. The test obtained a loading-unloading curve with a maximum compression strain of 80%, and obtained the compressive strength (σmax) at 80% strain, in kPa. Specific energy absorption (SEA), in KJ / m 3 g.
[0070] (2) Impact resistance test:
[0071] The drop hammer impact test method was used to conduct low-speed impact tests on different foam samples using a floor-standing drop hammer tester. This study used a hemispherical punch with a diameter of 16 mm. A force sensor with a range of 30 kN was installed inside the punch. The impact energy was 20 J, and the energy absorption efficiency (EAR) of each sample was calculated in %.
[0072] The raw materials used in the examples are:
[0073] Polyether polyols were purchased from Zhejiang Huafeng New Materials Co., Ltd.;
[0074] The isocyanate model is PM200;
[0075] The chain extender is ethylene glycol, which is commercially available;
[0076] The cross-linking agent was diethanolamine, which is commercially available;
[0077] The foam leveling agent is silicone oil, which is commercially available;
[0078] The catalyst was A33 (a gel-type polyurethane catalyst composed of 33% triethylenediamine and 67% dipropylene glycol (DPG) solution), purchased from Ye Innovation Materials (Shanghai) Co., Ltd.
[0079] Mould size: 10cm×10cm×5cm.
[0080] Example 1: Preparation of integrated gradient polyurethane foam material under constant load
[0081] The steps for preparing the integrated gradient polyurethane foam material under constant load are as follows:
[0082] (1) The polyether polyol, blowing agent (water), chain extender, crosslinking agent, foam leveling agent and catalyst were mixed in a mass ratio of 100:0.75:5:3:0.5:1.75 to obtain a prefabricated material; the prefabricated material and isocyanate were then mixed in a mass ratio of 111:80.75 to obtain a foamed material (191.75 g);
[0083] (2) The foaming material is placed in a mold. Within the processing window period, the surface of the foaming material in the lifting direction is used as the action surface. A mechanical load block with a finely controlled stroke and equal to the length and width of the mold is used to apply a step-by-step load to the foaming material. The load intensity is 10 bar, and the total constant load time is 3 seconds. After that, no load is applied and free foaming is performed for 7 seconds, so that the overall operation time matches the gelation time of the homogeneous foam (operation time = load time + free foaming; the gelation time is closely related to the properties of the substrate and is affected by the feed ratio. In this embodiment, the gelation time is 10 seconds); 1 minute after the foaming is completed, the foam sample is taken out and placed in a 50°C oven for aging for 48 hours to prepare an integrated gradient foam, sample number JT-1.
[0084] The scanning electron microscope image results of sample JT-1 are as follows Figure 1 shown.
[0085] Example 2: Preparation of integrated gradient polyurethane foam material under constant load
[0086] On the basis of Example 1, the constant load time in step (2) was changed to 6 s, the free foaming time was changed to 4 s, and the other conditions were consistent with Example 1 to prepare an integrated gradient foam, sample number JT-2.
[0087] The scanning electron microscope image results of sample JT-2 are as follows Figure 2 shown.
[0088] Example 3: Preparation of integrated gradient polyurethane foam material under constant load
[0089] On the basis of Example 1, the constant load time in step (2) was changed to 9 s, the free foaming time was changed to 1 s, and the other conditions were the same as those in Example 1 to prepare an integrated gradient foam, sample number JT-3.
[0090] The scanning electron microscope image results of sample JT-3 are as follows Figure 3 shown.
[0091] Example 4: Preparation of integrated gradient polyurethane foam material with gradient loading
[0092] The steps of preparing the integrated gradient polyurethane foam material with gradient loading are as follows:
[0093] (1) mixing polyether polyol, (foaming agent) water, chain extender, crosslinking agent, foam leveling agent and catalyst in a mass ratio of 100:0.75:5:3:0.5:1.75 to obtain a prefabricated material; and then mixing the prefabricated material and isocyanate in a mass ratio of 111:80.75 to obtain a foamed material;
[0094] (2) The foaming material is placed in a mold. Within the processing window period, a continuous load is applied to the foaming material with the surface in the lifting direction of the foaming material as the action surface; the load intensity starts from 0 bar and increases evenly to 10 bar, and the total time of the gradient load is 3 s (that is, the load intensity change rate is 3.33 bar / s). For another period of time, no load is applied at all for free foaming, so that the overall operation time matches the gelation time of the homogeneous foam; 1 minute after the foaming is completed, the foam sample is taken out and placed in a 50°C oven for aging for 48 hours to prepare an integrated gradient foam, sample number LX-1.
[0095] The scanning electron microscope image of sample LX-1 is shown in Figure 4 shown.
[0096] Example 5: Preparation of integrated gradient polyurethane foam material with gradient loading
[0097] On the basis of Example 4, the gradient loading time in step (2) was changed to 6 s, the free foaming time was changed to 4 s, and the other conditions were consistent with Example 4 to prepare an integrated gradient foam, sample number LX-2.
[0098] The scanning electron microscope image of sample LX-2 is shown in Figure 5 shown.
[0099] Example 6: Preparation of integrated gradient polyurethane foam material with gradient loading
[0100] On the basis of Example 4, the gradient loading time in step (2) was changed to 9 s, the free foaming time was changed to 1 s, and the other conditions were consistent with Example 4 to prepare an integrated gradient foam, sample number LX-3.
[0101] The scanning electron microscope image of sample LX-3 is shown in Figure 6 shown.
[0102] Comparative Example 1: No load applied
[0103] The polyurethane foam material was prepared without applying a load, and the steps were as follows:
[0104] (1) mixing polyether polyol, (foaming agent) water, chain extender, crosslinking agent, foam leveling agent and catalyst in a weight ratio of 100:0.75:5:3:0.5:1.75 to obtain a prefabricated material; and then mixing the prefabricated material and isocyanate in a weight ratio of 111:80.75 to obtain a foamed material;
[0105] (2) The foaming material is placed in a mold and allowed to foam freely. After the foaming is completed for 1 minute, the foam sample is taken out and placed in a 50°C oven for aging for 48 hours to obtain a homogeneous foam, sample number JZ-PUF.
[0106] The scanning electron microscope image results of the sample JZ-PUF are as follows Figure 7 shown.
[0107] Example 7: Testing the performance of integrated gradient foam
[0108] The integrated gradient foams prepared in Examples 1 to 6 and Comparative Example 1 were taken to test various properties.
[0109] (1) Microstructure parameters
[0110] The results of cell size, cell density and open / closed porosity are shown in Table 1. The results show that the integrated gradient foam prepared in Example 3 has the smallest cell size, the highest cell density and the lowest open / closed porosity, which is significantly better than other examples and comparative examples. The mass of all samples is similar, and the change in volume makes the average density vary greatly.
[0111] The density of integrated gradient foam is higher than that of homogeneous foam. This is due to the introduction of dense mass area. The higher the content of dense mass area, the greater the average density and the more obvious the gradient structure.
[0112] Therefore, integrated gradient foam can achieve or even exceed the performance of homogeneous foam with a smaller mass, thus saving material costs. The cell size, open porosity and cell density interact with each other and jointly determine the basic properties of the material. The open porosity reflects the openness of the cells, which has a potential impact on the stress transmission and absorption of the material. The high open porosity caused by cell merging will also increase the corresponding cell size. When the pore size increases, the cell density decreases. The smaller the cell size, the higher the cell density and the lower the open porosity, the more conducive it is for the foam material to exert its compression and impact resistance.
[0113] Table 1 Microstructure parameters
[0114]
[0115] (2) Protection performance test
[0116] The compressive strength and specific energy absorption results are shown in Table 2. The results show that the integrated gradient foam prepared in Example 3 has the highest compressive strength and specific energy absorption, which are significantly higher than those of other examples and comparative examples.
[0117] In terms of impact resistance, all samples showed high energy absorption efficiency above 97%. Although JT-3 is weaker than homogeneous foam in terms of EAR, which is the effect of the material structure characteristics, it is precisely because of the existence of the dense area that the dense structure is more conducive to resisting tearing, and the tear depth of the integrated gradient foam is much smaller than that of the homogeneous foam (Comparative Example 1). That is, JZ-PUF and the foam prepared by step load can dissipate energy by tearing, but this energy absorption method will shorten the service life of the material.
[0118] Table 2 Protection performance
[0119]
[0120]
[0121] It can be seen from the above data that the integrated gradient foam materials prepared in Examples 1 to 6 have greatly improved compression and impact protection properties compared with ordinary foam materials; and as the load increases, the pore size gradually decreases, the gradient difference increases, and the performance improvement is more significant.
[0122] Comparative Example 2: Changing the load intensity
[0123] (1) Based on Example 1, the load intensity was changed to 20 bar, and the other conditions were the same as those in Example 1.
[0124] The results showed that it was impossible to prepare an integrated gradient foam.
[0125] During the processing window, the molecular chains of the matrix are not fully networked, and their strength is insufficient to support excessive load strength. At the same time, the viscosity of the foam is still increasing, which will cause the bubbles to stick together and foaming to fail.
[0126] (2) Based on Example 1, the load intensity was changed to 1 bar, and the other conditions were consistent with Example 1.
[0127] The results showed that it was impossible to prepare an integrated gradient foam.
[0128] Since the pore wall is made of polymer macromolecular material and has a certain rigidity, the lower load is within the bearing strength range of the semi-formed pores, the pores will not deform, and the produced foam is a homogeneous foam.
[0129] Comparative Example 3: Changing the rate of change of load intensity
[0130] (1) Based on Example 4, the load intensity change rate was changed to 5 bar / s, and the other conditions were consistent with Example 1.
[0131] The results showed that it was impossible to prepare an integrated gradient foam.
[0132] When the load intensity change rate is higher than the foam lifting rate, the contact time with the substrate is insufficient, which is equivalent to no pressure-assisted foaming, and ordinary homogeneous foam is produced.
[0133] (1) Based on Example 4, the load intensity change rate was changed to 0.1 bar / s, and the other conditions were consistent with Example 1.
[0134] The results showed that it was impossible to prepare an integrated gradient foam.
[0135] When the load variation rate is very slight, the load intensity hardly changes during the processing window, and its effect is similar to the mold cover of conventional homogeneous foam, which ultimately leads to the produced foam being a homogeneous foam.
[0136] Comparative Example 4: Free foaming before applying load
[0137] (1) Based on Example 1, the loading method in step (2) was changed as follows: first free foaming for 7 seconds, and then applying a constant load for 3 seconds (the load intensity was 10 bar). The other conditions were consistent with Example 1.
[0138] The results showed that it was impossible to produce an integrated gradient foam.
[0139] (2) On the basis of Example 4, the loading mode in step (2) is changed as follows: free foaming for 7 seconds, and then a gradient load is applied for 3 seconds (the load intensity starts from 0 bar and increases evenly to 10 bar, that is, the load intensity change rate is 3.33 bar / s), and the other conditions are consistent with Example 1.
[0140] The results showed that it was impossible to produce an integrated gradient foam.
[0141] The reasons why integrated gradient foam cannot be produced by processes (1) and (2) are similar: no matter how the subsequent auxiliary load changes, as long as free rise is performed first, the substrate will reach a semi-gel state before the load acts, and the structural strength of the pores will increase, making it difficult for the substrate to maintain its deformed shape. The deformation at this time is elastic deformation, and the deformed pores return to their original shape after the load is removed. Therefore, the foam produced is still a homogeneous foam.
[0142] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing an integrated gradient polyurethane foam, characterized in that: The method comprises: (1) mixing a polyether polyol, a blowing agent, a chain extender, a crosslinking agent, a foaming agent and a catalyst to obtain a prefabricated material; mixing the prefabricated material and an isocyanate to obtain a foamed material; (2) pouring the foaming material into a mold, applying a load to the surface of the foaming material in the lifting direction as the action surface; after the load is applied, free foaming is performed; after the foaming is completed, taking out the foam sample, and ripening it to obtain an integrated gradient polyurethane foam; Among them, the load intensity during the load action is 8 to 12 bar, the constant load is 2 to 10 seconds, and the free foaming is 0 to 8 seconds; or, During the load action, the load intensity starts from 0 bar, and the load intensity changes at a rate of 0.8 to 4.0 bar / s, with a gradient load of 2 to 10 s and free foaming of 0 to 8 s.
2. The method according to claim 1, characterized in that In step (1), the mass ratio of polyether polyol, foaming agent, chain extender, crosslinking agent, foam leveling agent and catalyst is 90-110:0.65-0.85:4-6:2-4:0.3-0.7:1.5-2.
3. The method according to claim 1, characterized in that In step (1), the mass ratio of the prefabricated material to the isocyanate is 98.45-123.55:75-86.
5.
4. The method according to claim 1, characterized in that In step (2), the aging is performed by placing the foam sample at 40 to 70° C. for 48 to 72 hours.
5. The integrated gradient polyurethane foam prepared by the method according to any one of claims 1 to 4.
6. Use of the method according to any one of claims 1 to 4 or the integrated gradient polyurethane foam according to claim 5 in the field of materials.
7. The use according to claim 6, characterized in that: The application of the material field includes: preparing building materials, furniture, packaging materials, protective equipment, medical equipment or sports equipment.
8. A pad for impact protection, characterized in that: The cushion comprises the integrated gradient polyurethane foam of claim 5 .
9. A building material, characterized in that: The building material contains the integrated gradient polyurethane foam according to claim 5.
10. A method for improving the compressive strength, specific energy absorption performance and impact resistance of polyurethane foam materials, characterized in that: The method comprises: (1) mixing a polyether polyol, a blowing agent, a chain extender, a crosslinking agent, a foaming agent and a catalyst to obtain a prefabricated material; mixing the prefabricated material and an isocyanate to obtain a foamed material; (2) pouring the foaming material into a mold, applying a load to the surface of the foaming material in the lifting direction as the action surface; after the load is applied, free foaming is performed; after the foaming is completed, taking out the foam sample, and ripening it to obtain an integrated gradient polyurethane foam; Among them, the load intensity during the load action is 8 to 12 bar, the constant load is 2 to 10 seconds, and the free foaming is 0 to 8 seconds; or, During the load action, the load intensity starts from 0 bar, and the load intensity changes at a rate of 0.8 to 4.0 bar / s, with gradient loading for 2 to 10 s and free foaming for 0 to 8 s.
Citation Information
Patent Citations
Composite foaming material with functionally gradient change structure as well as preparation method and application thereof
CN110483720A
Polyurethane composite material for multi-path comfortable shoe material and preparation method of polyurethane composite material
CN116178781A
Preparation method and application of multi-layer gradient foam
CN117820714A
Polyurethane foam
US20140193631A1
Method for the synthesis of an auxetic polyurethane foam with a defined cell structure and auxetic polyurethane foam obtainable by the method
US20230192938A1
Cited By
Polyurethane soft foam with vertical gradient hardness as well as preparation method and application thereof
CN120554607A
Polyurethane elastomer anti-vibration pad
CN120757742A
